Adverse Maternal outcomes: A concept analysis - Chimbetete, Sheila; Ncube, Francis; Ndaimani, Augustine; Mugadza, Gladys; Kapfunde, Abigail; Zvinavashe, Mathilda; Gwariro, Simba; Haruzivishe, Clara (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Obstructed labor is a common cause of maternal and neonatal morbidity and deaths worldwide.It is responsible for up to 8% of maternal deaths in the world. Other causes of maternal deathssuch as postpartum hemorrhage and puerperal sepsis are closely linked to the abnormal course oflabor. Postpartum hemorrhage is a cause for 10-60% of maternal deaths globally (Salama et al,2010).According to Zimbabwe Demographic Survey, (2010-2011) maternal mortality ratio was960 and now currently 614 according to Multi Indicator Cluster Survey, (2014). The purpose ofthis article is to analyse the concept of adverse maternal outcomes and explore implications forpractice using Walker and Avant’s eight step approach analysis. The major defining attributeshat were identified were undesirable, unfavourable, harmful, severe, life threatening outcomessuch as antepartum haemorrhage, postpartum haemorrhage, eclampsia and obstructed labour andthese require accurate diagnosis as well as urgent intervention. Some of the identifiedantecedents were extreme maternal age, unbooked for antenatal services, pregnancy inducedhypertension, socioeconomic factors, cephalo-pelvic disproportion and malpresentation.Common cited consequences were renal failure, disseminated intravascular coagulation,hypovolemic shock and maternal death The study findings are of significance in future researchstudies and the need to strengthen interventions that reduce the occurrence of maternal adverseoutcomes